Study characteristics. - Kaylee P. Kruzan (7949414) (2025)
Nonsuicidal self-injury (NSSI) is a complex behavior, and its presentation is marked by significant heterogeneity, complicating efforts to identify and intervene. In this study, we sought to systematically review studies that used data-driven classification methods to identify NSSI subgroups. We searched PubMed, MEDLINE, EMBASE, PsycINFO, Web of Science, and Scopus. Article were included if they: (1) focused on NSSI, relative to suicidal self-injury, (2) were published in a peer-reviewed journal, (3) in English language, (4) applied data-driven classification methods to identify subgroups of NSSI and (5) provided details about building the analytical models. Two investigators independently screened abstracts and full-text articles and assessed study quality. In total, 26 articles published between 2008 and 2023 were identified by the search. Studies included data from 7,388 individuals with a history of NSSI and identified 94 subgroups. Many subgroups were defined by NSSI characteristics including NSSI methods, NSSI functions, and lifetime frequency. Others focused on emotion regulation, social competencies, or relationship quality. The quality of study designs and reporting varied. Understanding heterogeneity within NSSI through these subgroups can help inform treatment and intervention personalization.